Compassion on university degree programmes at a UK university: The neuroscience of effective group work. Issue 1 (4th June 2018) - Gilbert, Theo; Doolan, NTF, Martina; Beka, Sylvia; Spencer, Neil; Crotta, Matteo; Davari, Soheil
Abstract : Purpose: The purpose of this paper is to explore the neuroscience that underpins the psychology of compassion as a competency. The authors explain why this cognitive competency is now taught and assessed on modules of different degree subjects in a UK university. Design/methodology/approach: The paper is divided into first, an exploration of recent psychology and neuroscience literature that illuminates the differences, and relationship, between empathy and compassion for safeness building in teams. Within that, the role of oxytocin in achieving social and intellectual rewards though the exercise of cognitive flexibility, working memory and impulsive inhibitory control (Zelazo et al., 2016) is also identified. The literature findings are compared against relevant qualitative data from the above university, so far, nine years of mixed methods action research on compassion-focussed pedagogy (CfP). Findings: These are that the concept and practice of embedding compassion as an assessed cognitive competency in university group work is illuminated and rationalised by research findings in neuroscience. Research limitations/implications: The limitations of the study are that, so far, fMRI research methods have not been used to investigate student subjects involved in the CfP now in use. Practical implications: The paper has implications for theory, policy and practice in relation to managing the increasing amount of group work that accompanies widening participation in higher education (HE). Social implications: The social implications of what is outlined in the paper pertain to student mental health, and academic achievement; to policy and practice for HE curriculum design across subjects and disciplines; and for the HE remit to serve the public good. Originality/value: A review of this kind specifically for student assessed group and its implications for student academic achievement and mental health has not, apparently, been published.